Polyhydroxylated [60]fullerene binds specifically to functional recognition sites on a monomeric and a dimeric ubiquitin1. Issue 16 (28th April 2015) - Zanzoni, Serena; Ceccon, Alberto; Assfalg, Michael; Singh, Rajesh K.; Fushman, David; D'Onofrio, Mariapina
<x xml:space="preserve">Abstract</x> Fullerenol binds specifically to a functional surface patch on ubiquitin, thereby preventing chain formation. The nanoparticle also interacts with a covalent ubiquitin dimer, targeting a physiological recognition site.